Pharmacokinetics of tecomin in rats after intragastric and intravenous administration. (21st September 2015) - Guo, Lina; Peng, Yushuai; Zhao, Can; Yang, Xin; Liu, Lijia; Wang, Rufeng
Abstract: The pharmacokinetics of tecomin, which is a potential bioactive compound from the flowers of Trollius chinensis, was studied. The results showed that this compound was easily absorbed and rapidly metabolized into veratric acid in vivo, and then the latter was eliminated slowly. In addition, the simulant in vitro gastrointestinal transformation experiments demonstrated that the basic enteral environment and intestinal bacterial flora also contributed to the metabolism of tecomin to veratric acid. Copyright © 2015 John Wiley & Sons, Ltd.